Frequency of suicide attempts and attitudes toward suicidal behaviour among doctors and nurses in Lagos, Nigeria - Olibamoyo, Olushola (S Afr J Psychiatr, 2020)
BACKGROUND: Competence and attitudes toward suicidal behaviour affect practice. These attitudes may influence the consideration of suicide during personal crisis among doctors and nurses. AIM: The attitudes of doctors and nurses towards suicidal behaviour was assessed using the Attitudes Toward Suicide Scale (ATTS), which was validated in another study by the authors, evaluated for the possible factors affecting this relationship and estimated the frequency of suicide attempts among doctors and nurses. SETTING: Lagos State University Teaching Hospital Lagos, Nigeria. METHODS: The cross-sectional survey about attitudes toward suicide was done among 226 doctors and nurses working at a tertiary institute hospital in Lagos, Nigeria, using the ATTS. Sociodemographic profile and self-rated competence, commitment, empathy and irritation toward suicide were obtained. Stratified random sampling was used, data were analysed using Statistical Package for Sociological Sciences. Data was summarised, reliability of the ATTS was assured and variables compared by t-test and ANOVA. Independent predictors were identified via multiple regression (p ≤ 0.05). RESULTS: Frequency of suicide attempts of 7.50% was found among respondents with a mean age of 35.84 ± 6.76 years. Attitudes toward suicidal behaviour were slightly positive (77.92 ± 9.90) and the independent predictors of less positive attitudes were nursing profession (β = 0.025, p < 0.001) and high self-rated irritation toward suicide (β = 0.18, p < 0.01). CONCLUSION: The frequency of suicide attempts is higher among doctors and nurses when compared to the general population. Doctors and nurses reported slightly positive attitudes toward suicidal behaviour with significant differences in the type of profession and levels of self-rated irritation toward suicide.